낙상 환자 관리 시뮬레이션 교육 프로그램 개발 및 평가 - 유미(Yu, Mi); 김종경(Jong Kyung); 김세영(Kim, Se Young); 조성현(Cho, Sung Hyun); 김명자(Kim, Myung Ja); 서문경애(Seomun, GyeongAe) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2017)
Purpose: This study was carried out to develop simulation scenarios for the management patient falls and to evaluate the effects of using the scenarios with student nurses. Methods: The research design was a quasi-experimental study using a methodology study. Study participants were 30 students who were in 4th year of nursing at one College of Nursing. Results: When comparing knowledge of falls before and after the simulation program, it was found that knowledge increased by 4.90 (from 24.60 pre-test to 29.50 post-test). For clinical performance of fall management, the score for assessment was 10.17 out of 16, for intervention 5.97 out of 10, and for evaluation 7.33 out of 8. The average score for reporting a fall to the doctor was 19.87 out of 30 based on SBAR. Prior to the implementation of the simulation program, the confidence of reporting to the physician was less than 5 in all four areas, but self-confidence improved by more than 6 points in all four areas after the program was implemented. Conclusion: Findings indicate that results of fall management simulation practice can contribute to nursing students' knowledge of falls, as well as to nursing interventions and post-treatment following a patient fall.